2014
DOI: 10.1111/ajd.12205
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in non‐melanoma skin cancer

Abstract: Basal cell carcinoma and squamous cell carcinoma are the most common malignancies and are classified under the umbrella of non-melanoma skin cancer (NMSC). NMSC exerts a small but appreciable decrement in quality of life (QOL). The impact posed may arise from the tumour itself or as a result of treatment, and through symptoms, functional limitations, cosmetic burden and auxiliary considerations such as cost and disturbance to the activities of daily living. Researchers have evaluated this burden using a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 34 publications
2
57
0
2
Order By: Relevance
“…In general, SCQOLIT scores were low suggesting that NMSC has a low impact on HRQOL which supports previous studies . However, a few patients reported SCQOLIT scores ≥ 20 suggesting it is a suitable tool to identify patients for which there is significant impact on HRQOL, who may need enhanced support.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In general, SCQOLIT scores were low suggesting that NMSC has a low impact on HRQOL which supports previous studies . However, a few patients reported SCQOLIT scores ≥ 20 suggesting it is a suitable tool to identify patients for which there is significant impact on HRQOL, who may need enhanced support.…”
Section: Discussionsupporting
confidence: 80%
“…Patient‐reported outcome measures (PROMs) offer potential to improve the quality of dermatology services in the National Health Service (NHS) by providing validated evidence from the patient perspective. The incidence of non‐melanoma skin cancers (NMSCs) is exponentially increasing and although rarely life‐threatening, both disease and treatments can have significant impact on health‐related quality of life (HRQOL) . Evaluating PROMs in NMSC is essential because of the impact on health and the burden on healthcare resources, yet there are few studies to date.…”
Section: Introductionmentioning
confidence: 99%
“…While this represents a massive disease burden on society, NMSC and AK tend to involve lower morbidity and mortality than malignant melanoma and can be treated or managed successfully in many cases. Still, treatment of BCC and SCC routinely involves surgery and –given the predominant occurrence of these cancers in sun‐exposed areas such as the face and scalp –surgical measures can be gruelling, stressful and cosmetically unfavourable for the patients …”
Section: Introductionmentioning
confidence: 99%
“…The numerous therapeutic options available for the treatment of AK are regarded as a valuable approach to SCC prevention . There is reason to assume that NMSC goes along with a reduction in health‐related quality of life (QL), and various studies have tried to quantify this reduction with various patient‐reported outcome measures (PROMs) . Still, no robust data set is available for German‐speaking countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nonmelanoma skin cancer is associated with a small but appreciable decrement in quality of life and accordingly this should be the outcome pursued. 16 Seidler's group used a simple probabilistic decision model to report that MMS was US$292 less expensive and yielded 0.056 additional QALYs compared with TE and was accordingly the dominant intervention. 5 From a health economics perspective, this is the best evidence to date regarding the costeffectiveness of MMS versus TE; however, further refinement such as the use of Markov modelling would improve the validity of the results obtained.…”
Section: Discussionmentioning
confidence: 99%